SIMON’S DISPLACEMENT IN THE GIFT (2015) MOVIE: A FREUDIAN PSYCHOANALYSIS - MIA DEWI FORTUNA, 121411233019 (2018)
This study endeavors to reveal the portrayal of displacement practices as self defense mechanism to cope with fear and anxiety. In relation to this matter, the childhood experiences become one of the most important stages of life where it will automatically affect the adulthood. In this case, if someone suffered from various traumatic events or maltreatments in his/her childhood, it will potentially construct anxiety and affect the personality development later. In accordance to this issue, the present study utilize Simon as the main character in The Gift movie as the main focus of the analysis because this character portrayed how someone can deal with their anxiety from his childhood stage by doing the practice of displacement. This study uses qualitative research as the method. In analyzing the data, the writer uses narrative and non-narrative of film analysis to support the study in order to gain deeper analysis. Freudian psychoanalysis becomes the main theory of this study. The writer focuses to emphasize more on anxiety and displacement for the theory. As the result, this study figures out that The Gift movie portrays the issue that traumatic events in childhood affects personality and how people behave to become an aggressive person as self defense in order to deal with their anxiety.